Mechanisms of aggression in women serving a sentence in a correctional facility - K. N. Shaklein; L. M. Bardenshteyn (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
In the work based on the study of 435 women with aggressive behavior, who is serving a sentence in a correctional facility, was to identify the basic mechanisms of aggressive behavior. The results of the study showed that the implementation mechanism of aggression is defined, to the greatest extent of clinical-psychopathological characteristics, which often play the role of a pivotal factor. In the context of the sentence the important role of personal, social factors and factors related to conditions of imprisonment, whose role in the mechanism of aggressive behavior: dispositional, predispositional catalyzing blocking provoking.